ANALISIS KINERJA JALAN DAN PERKERASAAN LENTUR AKIBAT PENGARUH MUATAN LEBIH (OVERLOADING) - Rikki Andreanus Situmorang; Puji Wibawa Wartadinata; Bagus Hario Setiadji; Supriyono Supriyono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Semarang roads - Kendal, which is part of the North Coast, an arterial road linking central basis of national economic activity. With the increased traffic on North Coast Road, and included on this road, especially with the presence of a growing number of trucks that are overweight overloaded on this road, so for the next few years is expected to be down this path of service, either in terms of traffic performance and the performance of the pavement. Given these problems, this study is conducted to evaluate the performance of road traffic Semarang - Kendal and estimate the need for the added layer of the existing pavement as a result of overloading (overloading) is. For purposes of analysis, the method used in this research capacity (MKJI) to analyze traffic performance, and methods of Highways 2002 to analyze the needs of additional layers as a result of overloading. From the results of the analysis, found that the value of the performance of the traffic for the roads to be reviewed on line Semarang - Kendal, the value of DS = 0.74 in 2019, while in the opposite lane (Kendal - Semarang) DS values obtained larger is equal to 0.79; thus advisable to increase the geometric path (such as road widening) or by shifting part of the burden to the rail mode as a solution to improve traffic performance in the coming years. As for the analysis of the existing pavement, this study used two types of load, which is ideal load (with reference to the amount of the allowable load or JBI) and actual load (of the survey). The analysis showed that in the year 2019 plan, the road Semarang - Kendal takes a thick layer added by 6 cm (for ideal weight) and 10 cm (for actual expenses). If the residual life analysis, then by applying the actual load on the existing pavement was found that the existing pavement structure can only support the weight overload for 4 years and 2 months of age 10-year plan.